2017
DOI: 10.1242/bio.026955
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the exopolysaccharide and growth rate on the morphogenesis of the terrestrial filamentous cyanobacterium Nostoc flagelliforme

Abstract: The terrestrial cyanobacterium Nostoc flagelliforme, which contributes to carbon and nitrogen supplies in arid and semi-arid regions, adopts a filamentous colony form. Owing to its herbal and dietary values, this species has been overexploited. Largely due to the lack of understanding on its morphogenesis, artificial cultivation has not been achieved. Additionally, it may serve as a useful model for recognizing the morphological adaptation of colonial cyanobacteria in terrestrial niches. However, it shows very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…They are structurally similar to Gram-negative bacteria, although some features and thickness of peptidoglycan resemble Gram-positive bacteria. In nature, cyanobacterial EPS can play a variety of functions such as adhesive, structural, protection against abiotic stress, bio weathering processes, gliding motility, and nutrient repositories in phototrophic biofilms or biological soil crusts [22][23][24]. The excretion of EPS, and in particular CPS, can occur via a junctional pore complex (JPC).…”
Section: Ecologymentioning
confidence: 99%
“…They are structurally similar to Gram-negative bacteria, although some features and thickness of peptidoglycan resemble Gram-positive bacteria. In nature, cyanobacterial EPS can play a variety of functions such as adhesive, structural, protection against abiotic stress, bio weathering processes, gliding motility, and nutrient repositories in phototrophic biofilms or biological soil crusts [22][23][24]. The excretion of EPS, and in particular CPS, can occur via a junctional pore complex (JPC).…”
Section: Ecologymentioning
confidence: 99%
“…Hence, an increasing number of researchers are focusing on how to increase cyanobacterial bioproducts yields by optimizing specific culture conditions, such as light, pH, carbon source and nitrogen source (Andersen, 2005;Xu et al, 2019). This is closely linked to the species physiology and the requirements of each growth phase, lag and exponential (Crnkovic et al, 2017;Cui et al, 2017). Cellular division during these growth phases depends on light and nutrient availability, as those are vital for the photosynthetic system (Barsanti & Gualtieri, 2006;Celekli et al, 2009;De Oliveira et al, 2014;Crnkovic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In nitrogen-deficiency medium, the N. flagelliforme culture treated with 0.2 W•m −2 UV-B for 30 days produced nearly 5 times more scytonemin than the nontreated samples. It was also observed that a light of 60-90 µmol photons•m −2 •s −1 induced the production of scytonemin in the exopolysaccharides of N. flagelliforme culture [23].…”
Section: Abiotic Factors Involved In the Induced Biosynthesis Of Scytoneminmentioning
confidence: 89%
“…Scytonemin does not dissolve in water, but dissolves readily in lipids. In liquid suspension culture of Nostoc flagelliforme, yellow-brown scytonemin was observed to be tightly associated with the released exopolysaccharides [23]. Scytonemin was usually extracted from samples with solvents such as 100% acetone or 100% ethyl acetate [11], 100% acetonitrile [24], 80% tetrahydrofuran [13], and methanol:ethyl acetate (1:1, v/v) [9,21].…”
Section: Solubility and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation